Self-Efficacy and Self-Regulated Learning among College Students in Digital Learning: A Meta-analytic Study - Aji Bagus Priyambodo; Fitri Andriani; Pramesti Pradna Paramita (Universitas Ahmad Dahlan, 2025)
The success of students in digital learning depends largely on internal psychological factors such as self-efficacy and self-regulated learning (SRL). However, the strength and consistency of the relationship between these two constructs vary across studies. This meta-analysis synthesizes findings from seven empirical studies (total N = 1,971) published between 2020 and 2024 to estimate the magnitude of the relationship between self-efficacy and SRL among university students in digital learning contexts. Data were analyzed using the Sidik–Jonkman estimator model in Jamovi. Results revealed a large and significant overall effect size (r = 0.66, p < .001; 95% CI [0.29, 1.03]) with high heterogeneity (I² = 97.6%, Q = 221.73, p < .001). Publication bias analysis indicated no significant bias (Egger’s regression test p = .896; Fail-safe N = 1,861). This study extends previous correlational research by providing quantitative evidence on the robustness of the link between self-efficacy and SRL specifically in digital learning environments. The findings contribute to a deeper understanding of how students’ confidence in their learning abilities supports the development of effective self-regulation strategies, thereby informing future interventions to enhance digital learning outcomes in higher education.